Korelasi Kadar Protein C-Reaktif dengan Rasio Kolesterol Total / HDL pada Penyandang Obes di RSUP Dr M Djamil Padang - Nanda Oktavia; Ellyza Nasrul; Efrida Efrida (Jurnal Kesehatan Andalas, 2021)
C-reactive protein is an acute-phase protein produced by the liver in response to inflammation. Dyslipidemia can trigger the inflammatory reaction in the blood vessels, causing atherosclerosis. The ratio of total cholesterol/High Density Lipoprotein (HDL) is considered as one of the sensitive predictor lipid ratio for the cardiovascular disease risk factor. Objectives: To determined the correlation of C reactive protein between cholesterol levels with total cholesterol/HDL ratio in obese people. Methods: This study was an analytical study with a cross-sectional design of 59 people who met the inclusion and exclusion criteria at the RSUP Dr. M. Djamil Padang from January to September 2019. Research subjects consisted of first degree obesity (25.0 ≤IMT <30.0 kg/m2) and second degree (≥30.0 kg/m2). C reactive protein levels were measured as high-sensitivity C-reactive protein. Total cholesterol and HDL levels were measured using automated clinical chemicals with the enzymatic colorimetric method. Data were analyzed by Pearson, significant if p <0.05. Results: The study subjects were 59 people (17 men and 22 women) with an average age was 35 (8.04) years. CRP levels in stage II obesity were slightly higher than grade I, with a mean difference between groups of 0.26 mg/L (95% CI: -1.80-1.2; p=0.74). The average ratio of total cholesterol/HDL levels in the obese group I and II was 5.13 and 4.80 (p=0.93). The correlation showed a very weak positive (r=0.12) and was statistically not significant (p=0.35). The results of the subanalysis showed relatively similar patterns between the first-degree obesity population (r=0.10; p=0.58) and second-degree (r=0.16; p=0.41). Conclusion: There is no significant correlation between protein C-reactive and total cholesterol/HDL ratio.Keywords: Obesity, C-Reactive Protein, total cholesterol/HDL ratio